The Power of Suggestion : Narrative and Notation in Contemporary Drawing. - Butler, Cornelia H. (Los Angeles : Museum of Contemporary Art, 1996)
Antezzo, Matthew ; Bishton, Ginny ; Cranston, Meg ; Crotty, Russell ; Durant, Sam ; Fujiyoshi, Aki ; Grigely, Joseph ; Hayes, Paula ; Kersels, Martin ; Kwon, Sowon ; Sanchez, Pauline Stella ; Schimert, Kathleen ; Stark, Frances
biog. p. 39-
Engels
The Power of Suggestion : Narrative and Notation in Contemporary Drawing, Museum of Contemporary Art, Los Angeles, November 3 1996 - January 26, 1997
boek